2006
DOI: 10.1017/s0022112005007925
|View full text |Cite
|
Sign up to set email alerts
|

Passive propulsion in vortex wakes

Abstract: A dead fish is propelled upstream when its flexible body resonates with oncoming vortices formed in the wake of a bluff cylinder, despite being well outside the suction region of the cylinder. Within this passive propulsion mode, the body of the fish extracts sufficient energy from the oncoming vortices to develop thrust to overcome its own drag. In a similar turbulent wake and at roughly the same distance behind a bluff cylinder, a passively mounted high-aspect-ratio foil is also shown to propel itself upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
230
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(246 citation statements)
references
References 25 publications
12
230
1
3
Order By: Relevance
“…Yet, experimental evidence seems to suggest the existence of some mechanisms for passive stabilization in fish motion. For example, [3] reported upstream motion of anesthetized fish (undeniably passive) in vortical flows and mentioned that the elastic properties of the fish body are essential to achieve this motion. Indeed, the motion of elongated rigid bodies in unsteady flows is known to be passively unstable, see, for example, [15,8,20].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, experimental evidence seems to suggest the existence of some mechanisms for passive stabilization in fish motion. For example, [3] reported upstream motion of anesthetized fish (undeniably passive) in vortical flows and mentioned that the elastic properties of the fish body are essential to achieve this motion. Indeed, the motion of elongated rigid bodies in unsteady flows is known to be passively unstable, see, for example, [15,8,20].…”
Section: Introductionmentioning
confidence: 99%
“…Beal et al (2006) showed that dead trout can recover sufficient energy from the surrounding flow to allow it to passively swim upstream. Inspired by this observation, we propose a simple model to emulate the motion of a body in an externally generated vortex street.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…The second example examines the effect of the ambient vorticity, modeled using point vortices, on the net locomotion of a rigid body, [5]. This example is inspired by [1] where dead trout was reported to recover sufficient energy from the surrounding flow to allow it to passively swim upstream. Indeed, we identify configurations where even a rigid body (no elasticity) can swim passively in the direction opposite to the motion of vortices at no energy cost.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the columnar vortices do not remain straight, and under the influence of the vortex ring become significantly distorted. For vorticity control, where oncoming coherent vortices may be manipulated to either enhance forces or recover energy by downstream bodies (Gopalkrishnan et al 1994;Beal et al 2006), this poses difficulties since the orientation of shed columnar vortices does not remain predictable. Hence, finding ways to reduce three-dimensionality are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in fish swimming, it is shown that the caudal fin operates in the wake of upstream fins, gaining propulsive efficiency through interaction with the oncoming vortices (Zhu et al 2002). The ability of bodies to extract energy from oncoming coherent vortices has been demonstrated in Beal et al (2006), who showed that a dead trout can extract energy from the coherent vortices of an oncoming Karman street wake generated by a D-shaped cylinder, causing it to surge upstream. The same results were demonstrated with a passive foil in the wake behind a D-shaped cylinder.…”
Section: Introductionmentioning
confidence: 99%